Climate, capital, class and crisis. (June 2020) - Clarke, Richard
Abstract : The extent of the environmental crisis — most apparent in climate change — has raised in sharp focus the relation between humans and nature as one of the central contradictions in capitalism. The monetisation of nature is one of the principal features of financialised capital, with carbon trading now one of the world's major commodity markets. At the same time, the environment is a focus for new alliances in the struggle for socialism.